2018
DOI: 10.1016/j.bbmt.2017.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Exposure to Zika Virus and Impact on Cord Blood Banking and Adult Unrelated Donors in Hematopoietic Cell Transplantation: The Canadian Blood Services Experience

Abstract: Zika virus has emerged as a potential threat to the Canadian blood supply system. Stem cell donors within Canadian Blood Services' Cord Blood Bank (CBB) and OneMatch Stem Cell and Marrow Network (OM) now undergo screening measures designed to reduce the risk of Zika virus transmission. The impact these screening measures have on cord blood and unrelated adult stem cell donations is currently unknown. Among 146 donor workups initiated by OM between July 2016 and May 2017, 102 were completed and 44 workups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These CBUs were discarded and not used in transplant. 19 , 20 Another study by the National Cord Blood Program, a public CBB, at New York Blood Center found that 27.5% of units collected from March 2016-December 2018 were ineligible for licensure, and, of these, 76% CBUs were ineligible due to ZIKV-related risk factors. 19 , 21 Of the 196 respondents to a 1-year follow-up survey sent to donors who had ZIKV risk, all mothers reported their infants were healthy.…”
Section: Discussionmentioning
confidence: 99%
“…These CBUs were discarded and not used in transplant. 19 , 20 Another study by the National Cord Blood Program, a public CBB, at New York Blood Center found that 27.5% of units collected from March 2016-December 2018 were ineligible for licensure, and, of these, 76% CBUs were ineligible due to ZIKV-related risk factors. 19 , 21 Of the 196 respondents to a 1-year follow-up survey sent to donors who had ZIKV risk, all mothers reported their infants were healthy.…”
Section: Discussionmentioning
confidence: 99%
“…The first study demonstrated that 25 of 875 mothers (2.9%) in Canada who donated their infant's cord blood had at least one risk factor for ZIKV exposure. However, none of the women had a documented ZIKV diagnosis during their pregnancies, and none of these UCB units were transplanted (all were discarded) . The second study, conducted by the New York Blood Center, showed that 27.5% of 4153 UCB units from March 2016 to December 2018 were from ineligible donors.…”
Section: Ucb Regulation and Zikv Screeningmentioning
confidence: 99%